2022
DOI: 10.1002/cdq.12291
|View full text |Cite
|
Sign up to set email alerts
|

Women of Color and decent work: An examination of psychology of working theory

Abstract: Women of Color (WOC) in the United States experience a unique form of intersecting oppression in the realm of work. Various previous studies have shown that WOC experience work objectively (e.g., wage disparity) and subjectively (e.g., compromised job satisfaction) differently than White women or Men of Color, indicating that WOC is less likely to attain decent work than their counterparts. In the present study, using psychology of working theory as the theoretical framework, we examined the predictors and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Previous PWT investigations with cross-sectional samples comprising Black-identified individuals demonstrated a direct relationship between marginalization and decent work. More specifically, Duffy and colleagues used GED (Duffy et al, 2018) and Kim and colleagues (2022) used the 3-item Lifetime Experiences of Marginalization Scale (LEMS). Perhaps, a less sophisticated measure like LEMS is better able to capture REM’s experiences of marginalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous PWT investigations with cross-sectional samples comprising Black-identified individuals demonstrated a direct relationship between marginalization and decent work. More specifically, Duffy and colleagues used GED (Duffy et al, 2018) and Kim and colleagues (2022) used the 3-item Lifetime Experiences of Marginalization Scale (LEMS). Perhaps, a less sophisticated measure like LEMS is better able to capture REM’s experiences of marginalization.…”
Section: Discussionmentioning
confidence: 99%
“…The volition subscale is comprised of four items and taps into one’s general sense of volition (as opposed to the other two subscales which tap into financial and structural barriers). The use of this subscale is common practice in PWT investigations with REM (e.g., see Kim et al, 2022). Example items include “I will be able to choose jobs that I want” and “I will learn how to find my own way in the world of work.” Items were measured on a 7-point scale ranging from 1 ( Strongly Disagree ) to 7 ( Strongly Agree ).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of the PWT as a theory for understanding a variety of workers' lives has been substantiated through research on several specific populations over the past few decades. For instance, research has shown that PWT is applicable for groups such as Korean emerging adults (Kim et al, 2019), sexual minorities (Douglass et al, 2017), and women of color (Kim et al, 2022). In each of these studies, PWT has served as an appropriate framework for enhancing scholarly understanding of individuals' workplace experiences, particularly in the attainment of decent work.…”
Section: Decent Work and Psychology Of Working Theorymentioning
confidence: 99%
“…In each of these studies, PWT has served as an appropriate framework for enhancing scholarly understanding of individuals' workplace experiences, particularly in the attainment of decent work. Many studies in the PWT literature have underscored the inverse relationship between lifetime marginalization/economic constraints and decent work, highlighting how groups who experience more direct or indirect marginalization in their lifetimes have less access to decent work due to lower levels of work volition, or perceived control over their work decisions (Kim et al, 2022). Overall, the PWT literature has continued to emphasize the important role of decent work in promoting key workplace needs, one of which is self-determination.…”
Section: Decent Work and Psychology Of Working Theorymentioning
confidence: 99%
“…It is based on the above research conclusions, in order to improve the environmental comfort of the residential area, this paper introduces the psychological theory into the environmental design of the residential area. Typical psychological theories mainly include cognitive system model and Gestalt psychology [ 11 13 ], color psychology [ 14 16 ], cognitive psychology [ 17 19 ], ecological self-consciousness theory [ 20 ], and probability self-consciousness theory [ 21 ]. Gestalt psychology is most widely and successfully used in interaction design.…”
Section: Introductionmentioning
confidence: 99%